L'ultimo canto del cigno Il delitto Notarbartolo a Firenze (un processo di mafia) - De Troja, Elisabetta (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2019)
The murder of Emanuele Notarbartolo, former director of the Banco di Palermo, at the hands of the Sicilian Mafia in 1893 represents a controversial and obscure event in Italian history. There were three trials (Milan, Bologna, Florence), which also involved a Sicilian deputy: Raffaele Palizzolo. Anna Franchi's documentation work takes place in the Assize court of Florence: she attended every hearing, and observed relentlessly both the 'Mafia' phenomenon and the actual theatre of testimonies, confessions, retractions and false tracks characterising the trial in Florence (1903-1904). It was possible to widely integrate Franchi's account after the discovery of the entire folder relating to the process in the State Archives of Florence: about 1500 handwritten pages by the various chancellors dealing with the trial. The trial ended in a general acquittal for principals and executors for lack of evidence. For some, Sicily's honour was safe, but for many others, the truth was forever covered up.